Mathematical Model of Non-Stationary Hydraulic Processes Occurring in Gas Centrifuges for Uranium Enrichment; Computation, Automation, Information Technologies and Safety Systems in Nuclear Industry; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Orlov A. A. Aleksey Alekseevich (Radiation Technologies in Medicine, 2015)
Title screen